Peran UMKM dalam Pembangunan dan Kesejahteraan Masyarakat Kelurahan Ngipik, Kabupaten Gresik - Istivarini, Diva; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
Micro, Small and Medium Enterprises (MSME) have a very important role in the development andwelfare of society. MSME are not only the backbone of the local economy, but also contributesignificantly to national economic growth. Through creating jobs, increasing income, and increasingpeople's access to goods and services, MSME provide a broad positive impact. In the context ofdevelopment, MSME play a vital role in reducing unemployment rates, improving workforce skills,and reducing economic disparities between regions. Apart from that, MSME also support economicdiversification by introducing unique local products and services to the global market. In terms ofcommunity welfare, MSME provide opportunities for local entrepreneurs, especially women andyouth, to start and develop their own businesses.Keywords: MSME; Development; Public Welfare; Government